Advanced gastrointestinal stromal tumor patients benefit from palliative surgery after tyrosine kinase inhibitors therapy. Issue 2 (January 2018) - Qiu, Hai-Bo; Zhou, Zhong-Guo; Feng, Xing-Yu; Liu, Xue-Chao; Guo, Jing; Ma, Ming-Zhe; Chen, Ying-Bo; Sun, Xiao-Wei; Zhou, Zhi-Wei
Abstract : Abstract: The role of palliative surgery is controversial in advanced gastrointestinal stromal tumors (GIST) after tyrosine kinase inhibitors (TKIs) therapy. We evaluated safety and clinical outcomes in a single institution series of advanced GIST patients from January 2002 to December 2008. One hundred and fifty-six patients had been recruited, including 87 patients underwent surgical resection and 69 patients kept on TKIs treatment. Four patients had major surgical complications. Median follow-up was 38.3 months, the overall survival (OS) and progression-free survival (PFS) of the patients in surgical group were longer than the nonsurgical group, PFS: 46.1 versus 33.8 months ( P < .01), OS: 54.8 versus 40.4 months. In the subgroup analysis for the patients received surgery, the median PFS for patients with progression disease, stable disease, and partial response was 33.3, 51.5, and 83.0 months, respectively ( P < .01). Median OS was 68.0 months in those with only liver or peritoneal metastases, and 45.3 months in those with both metastases. Median PFS of patients underwent R0/R1 resection was 73.6 months compared with 35.8 months in R2 resection patients ( P < .01). Patients with advanced GISTs have prolonged OS after debulking procedures. Surgery for patients who have responsive disease after TKIs treatment should be considered.